Correlation of serum TNF alpha level with severity of chronic obstructive pulmonary disease - S., Mathanraj; Kumar, Vysak; S., Yuvarajan; Reddy, Vikram (International Journal of Research in Medical Sciences, 2017)
Background: Tumor necrosis factor alpha (TNF α) is the most widely studied cytokine of TNF super family. TNF α plays a significant role in many inflammatory diseases affecting the lung, such as chronic bronchitis (CB), chronic obstructive pulmonary disease (COPD), asthma, acute lung injury (ALI) and acute respiratory distress syndrome. Elevated levels of TNF-alpha are seen in COPD patients. An increased level of TNF-α has been found in induced sputum or lung biopsy of COPD patients. 14-16 This study includes correlation of level of TNF α with severity and characterization of individuals with COPD. There are only limited numbers of studies being conducted regarding this topic in the world, including India. Objectives of present study were to measure the TNF-α level in patients with chronic obstructive pulmonary disease and to correlate TNF α level with severity of chronic obstructive pulmonary disease. Methods: The study was conducted on one hundred and eight (108) patient’s COPD patients attending the Pulmonary medicine department of Sri Manakula Vinayagar Medical College and Hospital Puducherry, who are aged above forty years, with a duration of 18 months, starting from the date of getting approval from the Ethics Committee. The subjects were analysed on their TLC, DLC was done to rule out any co-existing infections. Spirometry was done to confirm the diagnosis of COPD. Blood was taken from the confirmed COPD patients after getting their approval, for the estimation of serum TNF α level. Results: The Serum TNF alpha levels increases according to the COPD severity. The mean serum TNF alpha level in patients with mild obstruction, moderate obstruction, severe and very severe obstruction were 9.91+2.9, 21.25+4.8, 32.4+8.2 and 39.2+3.1pg/dl respectively. Mean TNF alpha value was 26.7pg/dl. The values of TNF α increases with the stages of COPD which is statistically significant with p value of 0.0001. Conclusions: The present study showed that serum TNF alpha level correlates with severity of airway obstruction in spirometry among the COPD patients. It also correlates with the disease severity as per the different stages of COPD patients (GOLD COPD staging 2016). Thus, serum TNF alpha is a useful marker to monitor the disease severity in addition to spirometric parameters like FVC, FEV1 and FEV1/FVC. However, further studies are needed with larger sample size.